“I’m Anxious when…”: Delving into Students’ Anxiety in EFL Online Instructions across School Levels - Santosa, Made Hery; Mali, Yustinus Calvin Gai (Jurnal Pendidikan Bahasa Inggris undiksha, 2024)
English instruction has been claimed to be challenging for some non-native students and with the addition of online environment, unpreprared students may experience anxiety, fear, or stress. This article aimed to analyse students’ anxiety across various school levels and explore their views from the anxiety components in EFL online instruction in Indonesia. Framed within a mixed methods research design, this study employed a large-scale survey of 928 students and an interview with 10 voluntary respondents. Data were collected using means of Foreign Language Classroom Anxiety (FLCAS) questionnaire and an interview guide. Using the validity check, 30 survey items were valid with a good fit (α=.89). Data from the questionnaire responses were analysed using SPSS to find frequencies of the respondents’ anxiety scores and categorized using Oetting’s Scale and the data from the interview transcripts were analysed using Interactive Model Analysis. The result showed students in various school levels were mildly anxious during the EFL online instruction. This means that students might be potentially anxious due to dynamic online learning situations when they attend their EFL instructions. Meanwhile, the interview revealed that they were anxious when having an English test and experiencing connection problems during online learning. They overcame them by learning the materials more and communicating their connectivity situations with the teachers. Teachers and policy makers should consider providing learning supports to deal with students’ anxiety in the virtual learning context.